2016
DOI: 10.18805/ijar.11325
|View full text |Cite
|
Sign up to set email alerts
|

Management practices and constraints of beef cattle production in communal areas of Mpumalanga Province, South Africa

Abstract: A survey study was conducted to determine the management practices and constraints faced by beef cattle producers in 200 households in communal areas of Chief Albert Luthuli Municipality in Mpumalanga province. In this context, the results indicated that while 91.5% of farmers practiced continuous breeding in heifers at younger than two years of age, a higher number approximately 68.5% of farmers relied upon neighbours for breeding bulls. Also, calving percentage was between 50% and 70% as reported by 43.5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…While 22.22 per cent of the farmers leave part of their Useable Agricultural Area (UAA) in fallow for feeding their livestock. While Molefi et al (2017) reported that 100 per cent of farmers freely grazed their beef cattle on the mountainside and over 93.5 per cent of farmers used veld as a source of feed in communal areas of Mpumalanga Province of South Africa. This finding was observed by Abbas and Abdelguerfi (2005) who reported that fallow is highly integrated in the livestock feeding system, which indicate the low level of integration of fodder crops in the semi-arid region.…”
Section: Results and Discussion Description Of Dairy Farmers Surveyedmentioning
confidence: 99%
“…While 22.22 per cent of the farmers leave part of their Useable Agricultural Area (UAA) in fallow for feeding their livestock. While Molefi et al (2017) reported that 100 per cent of farmers freely grazed their beef cattle on the mountainside and over 93.5 per cent of farmers used veld as a source of feed in communal areas of Mpumalanga Province of South Africa. This finding was observed by Abbas and Abdelguerfi (2005) who reported that fallow is highly integrated in the livestock feeding system, which indicate the low level of integration of fodder crops in the semi-arid region.…”
Section: Results and Discussion Description Of Dairy Farmers Surveyedmentioning
confidence: 99%
“…The province is home to just over 5 million people (Census 2011). It has a sub-tropical climate with hot summers and mild to cold winters where the average daily temperature in summer is 24 and 14.8°C in winter (Mpumalanga Department of Agriculture, Conservation and Environment 2003; Mpumalanga Department of Agriculture, Rural Development and Land and Environmental Affairs 2012; Molefi et al 2017). Furthermore, their average rainfall is 767 mm per annum with approximately 10 times more rainfall in summer than in winter.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…In South Africa, rural cattle production comprises about 40% of the national herd (DAFF 2017;Molefi et al 2017). Cattle farming is popular in rural areas because of the multiple benefits that cattle provide to the households which include the provision of meat, milk, skin, draught power, fertiliser, payment of lobola and cash generation through sales (Dreyer et al 1999;Randela 2003;Delali et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that weaning percentage is one of the primary factors in the profitability of cow-calf outfits and several factors including experience in cattle farming, population of herd, age at mating, calving percentage, weaning age, supplementary feeding, internal and external disease management etc. which if not properly handled, will likely lead to reduced body condition and poor reproductive performance of breeder cows (Molefi et al, 2017), resulting in low productivity (Blanco et al, 2008;Waterman et al, 2012). Weaning percentage, as defined by (NCBA, 1992) and used by the Standardized Performance Analysis tool, is simply a ratio of live calves weaned to adjusted number of females exposed to mating during the breeding season (Mousel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile among the breeding cows, mortality is twice as high in heifers as in adult cows (Goyache et al, 2003;Harbers et al, 2000;Meyer et al, 2001). (Bergh, 2013;Molefi et al, 2017) highlighted many factors that could influences weaning percentage in beef and dairy farm operations. But factors influencing weaning percentage are specific to the environment and unique to Improved Cattle Production Parameter Drivers Among Farmers in Mpumalanga Province of South Africa every outfit (Beffa et al, 2009;Blanco et al, 2008).…”
Section: Introductionmentioning
confidence: 99%